2014
DOI: 10.1155/2014/960803
|View full text |Cite
|
Sign up to set email alerts
|

How to Take Autophagy and Endocytosis Up a Notch

Abstract: The interconnection of the endocytic and autophagosomal trafficking routes has been recognized more than two decades ago with both pathways using a set of identical effector proteins and sharing the same ultimate lysosomal destination. More recent data sheds light onto how other pathways are intertwined into this network, and how degradation via the endosomal/autophagosomal system may affect signaling pathways in multicellular organisms. Here, we briefly review the common features of autophagy and endocytosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 129 publications
(186 reference statements)
1
22
0
2
Order By: Relevance
“…Besides confirming these results, we found a detectable association of endogenous Ulk3-Gli2 in HDFs and showed that increased ulk3 expression was both required and sufficient for Gli and CAF activation. Separately from this, we uncovered an interplay between CSL and Ulk3 in control of autophagy that may apply, with context-dependent adjustments, to other cellular systems in which Notch signaling has been pharmacologically implicated (Barth and Kohler, 2014; Chen et al, 2016; Song et al, 2015; Yao et al, 2015). Importantly, while autophagy/mitophagy have been previously implicated in metabolic reprogramming of CAFs (Kim et al, 2011; Russell et al, 2013), our genetic evidence indicates that they are not significantly involved in the gene expression program leading to CAF activation.…”
Section: Discussionmentioning
confidence: 96%
“…Besides confirming these results, we found a detectable association of endogenous Ulk3-Gli2 in HDFs and showed that increased ulk3 expression was both required and sufficient for Gli and CAF activation. Separately from this, we uncovered an interplay between CSL and Ulk3 in control of autophagy that may apply, with context-dependent adjustments, to other cellular systems in which Notch signaling has been pharmacologically implicated (Barth and Kohler, 2014; Chen et al, 2016; Song et al, 2015; Yao et al, 2015). Importantly, while autophagy/mitophagy have been previously implicated in metabolic reprogramming of CAFs (Kim et al, 2011; Russell et al, 2013), our genetic evidence indicates that they are not significantly involved in the gene expression program leading to CAF activation.…”
Section: Discussionmentioning
confidence: 96%
“…58 Activation, regulation and degradation of the Notch signal require endosomal trafficking of both ligands and receptors. 59,60 Activation of the NOTCH pathway begins with binding of type 1 ligands from the DSL families (Delta, Jagged) to Notch transmembrane receptors, 6164 triggering a series of proteolytic cleavages within the plasma membrane and intracellular compartment, and initiating signal transduction. ADAM family proteins TACE (ADAM 17) and Kuzbanian (ADAM 10) mediate regulation of Notch extracellular domain shedding.…”
Section: Notch Is a Key Pathway In Prostate Cancermentioning
confidence: 99%
“…59,60 NUMB interacts with the AP-2 adaptor complex and the endocytic proteins α-adaptin and Eps15, in clathrin-coated pits and in endosomes. 133 This ability of NUMB to localize in endocytic organelles, cotraffic with internalizing receptors and physically interact with endocytic machinery has raised the possibility of NOTCH inhibition by NUMB through endocytosis.…”
Section: The Numb–notch Interactionmentioning
confidence: 99%
“…Recent investigations indicate that the endocytic pathway can promote efficient autophagy by promoting phagophore formation and expansion. In addition, the early endosomes, multivesicular bodies, or late endosomes can fuse with autophagosomes before their fusion with lysosomes . It is, therefore, speculated that endocytosis might play a role in ANE 30‐100K‐induced autophagy.…”
Section: Introductionmentioning
confidence: 99%